Roles And Responsibilities of Human Resource Management in Organizing The “Ranking 1” Event for Elementary School Students at Polbeng Business Expo Chapter Two - Wahyu Setia Neng Urep (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Human Resource Management (HRM) plays a significant role in ensuring the successful planning, implementation, and evaluation of an event. Effective human resource management enables event organizers to allocate responsibilities appropriately, improve coordination, and achieve organizational objectives efficiently. This study aims to analyze the roles and responsibilities of Human Resource Management in organizing the Ranking 1 Competition for elementary school students at the Polbeng Business Expo Chapter Two. A descriptive qualitative approach was employed to obtain an in-depth understanding of the human resource management practices implemented during the event. Data were collected through direct involvement, observation, documentation, and post-event evaluation conducted throughout the preparation and implementation stages. The event was organized at the State Polytechnic of Bengkalis from 20–22 May 2025, involving 62 elementary school students from grades four to six, supported by an organizing committee consisting of a Project Manager, Secretary, Finance Division, Marketing Division, Human Resource Division, Event Division, Equipment Division, Consumption Division, and operational volunteers. The findings indicate that Human Resource Management contributed significantly to identifying personnel requirements, determining participant and judge criteria, recruiting staff and volunteers, assigning responsibilities according to individual competencies, supervising event implementation, and conducting performance evaluations after the event. Effective communication, teamwork, and coordination among committee members were found to be essential factors contributing to the successful implementation of the competition despite several operational and logistical challenges encountered during the event. This study concludes that effective Human Resource Management enhances organizational performance, strengthens teamwork, minimizes overlapping responsibilities, and supports the successful implementation of educational events. The findings are expected to provide practical recommendations for improving human resource management practices in future student-organized events and similar educational activities.